Public anthropology: engaging social issues in the modern world - Hedican, Edward J. (University of Toronto press, 2016)
Contemporary anthropology has changed drastically in the new millennium, expanding beyond the anachronistic study of "primitive" societies to confront the burning social, economic, and political challenges of the day. In the process, anthropologists often come face to face with issues that require them to take a public position-issues such as race and tolerance, health and well-being, food security, reconciliation and public justice, global terror and militarism, and digital media This comprehensive but accessible book is both an interesting read and an excellent overview of public anthropology. In-depth case studies offer an opportunity to evaluate the pros and cons of engaging with public issues, while profiles of select anthropologists ensure the book is contemporary, but rooted in the history of the discipline.